Membangun Citra Perusahaan melalui Corporate Communication : Studi Kasus Klinik Pelangi Bunda Medika - Uswatun Hasanah; Dewi Ilma Agustin; Ani Gusliyani; Resa Rahmawati; Sisca Dwi Aprilia (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
This research aims to analyze how Pelangi Bunda Medika Clinic builds a positive corporate image through effective corporate communication strategies. A strong corporate image is very important, especially in the health sector, to increase patient confidence in the services provided. In this context, Pelangi Bunda Medika Clinic uses a planned communication approach through various channels, such as social media, website and customer service, to create a professional, safe and friendly impression in the eyes of the public. Through the implementation of integrated corporate communications, this clinic has succeeded in building an image as a caring, affordable and educational health service provider. This research also identified the obstacles faced, such as difficulties in updating information on digital platforms and competition with other clinics, as well as improvement steps taken by the clinic to increase communication effectiveness. The research results show that effective communication strategies can increase the number of patients and strengthen relationships with the community, as well as expand the dissemination of health service information. Recommendations include increasing digital presence, developing a patient loyalty program, and communications training for staff to increase the consistency of messages delivered. This research concludes that planned and professional corporate communications play an important role in strengthening the image and reputation of the Pelangi Bunda Medika Clinic.